Accelerating cryptographic computation with parallel computing mechanisms in Android platform - Ning FANG; Weibing CAO; Donghe NI; Guandong DI (网络与信息安全学报)
Aiming to accelerate cryptographic computation in Android platform,parallel computing method is adopted.Utilizing RenderScript framework in Android platform,big integer multiplication operation is implemented in parallel,which provides efficient and fast basic operations for cryptographic schemes such as elliptic curve.Storage structure and computing logic are designed and implemented for parallel computation of big integer multiplication.Integers are decomposed and handled as matrix elements,so that all additive and multiplicative operations can be performed simultaneously,which provides accelerated intermediate result for multiplication operations.Experiment results show that,compared to the original Java library for big integers in the Android platform,the proposed method has distinctive advantage in execution time.